SPECTRAL COMPRESSION OF FEMTOSECOND PULSES - Kutuzian, A. A. (Proceedings of the YSU A: Physical and Mathematical Sciences, 2004)
The influence of high-order dispersion and nonlinear effects on the spectral compression process is studied. This influence is revealed in the ≤ 50 fs time scale.